Associations between Starting to Exercise in Later Life and Survival among Older Adults: a Nationwide, Community-based, Prospective Cohort Study in China - Haiyan Ruan; Ziqiong Wang; Kexin Wang; Muxin Zhang; Sen He (Sports Medicine - Open)
Abstract Background Physical inactivity and prolonged sedentary behavior represent significant public health concerns that can be addressed to achieve considerable health benefits. However, it is unknown whether starting to exercise in later life is an effective intervention for promoting health and longevity in older adults who have not exercised previously. The study aimed to explore whether starting to exercise in later life could offer survival benefits for older adults (≥ 65 years), particularly focusing on the impact of exercise duration on survival. Methods A total of 23,889 older participants (median age: 91.0 [IQR: 82.0–100.0], 8760 males) from the Chinese Longitudinal Healthy Longevity Survey were included. Participants comprised non-exercisers who never exercised and regular exercisers who started to exercise regularly after age 65 for at least one year. The exposure was exercise duration, which was self-reported and categorized into four groups: non-exercise (0 years), 1 to < 10 years, 10 to < 20 years, and ≥ 20 years. The study outcome was overall survival. Accelerated failure time models were used to investigate the association between exercise duration and outcomes. Results During a follow-up period totaling 101118.9 person-years, there were 18,751 recorded deaths (78.5%). Overall, regular exercisers had longer survival time than non-exercisers, with an adjusted time ratio (TR) of 1.07 (95% CI: 1.03–1.11, p < 0.001). When compared to non-exercisers, the adjusted TRs for participants with varying exercise durations were as follows: 1.06 (95% CI: 0.99–1.14, p = 0.086) for those exercising between 1 and < 10 years, 1.03 (95% CI: 0.97–1.08, p = 0.382) for those between 10 and < 20 years, and significantly higher at 1.12 (95% CI: 1.05–1.18, p < 0.001) for those with ≥ 20 years of exercise duration. In addition, smooth curve fitting analysis also revealed the survival benefits of exercise were only significant for those with an exercise duration of ≥ 20 years, with an adjusted TR of 1.024 (95% CI: 1.013–1.036, p < 0.001) for each 5-year increase in duration. Conclusions Starting to exercise in later life can provide survival benefits for older adults, but only if they maintain exercise for over 20 years. This long latency period may suggest suboptimal exercise efficiency among older adults in real-world contexts; therefore, it is essential not only to emphasize the importance of long-term exercise but also to promote structured exercise within this population.